Analysis of regional-level basketball athletes’ understanding of official basketball rules - Mesya Arba Putra Hadi; Agus Wiyanto; Dani Slamet Pratama (Sriwijaya Journal of Sport, 2026)
Research Problems: Understanding serves as a fundamental foundation for developing knowledge and mastering subject matter, including in competitive sports contexts. In basketball competitions, official rules function as essential guidelines that must be understood and followed by all parties involved, including referees, coaches, and athletes. The official international regulations are established by FIBA (2022), which consist of eight principal rules and fifty technical provisions. However, the extent to which athletes understand these regulations, particularly in the POPDA Grobogan competition, has not been clearly identified. Research Objectives: Therefore, this study aimed to analyze the level of athletes’ understanding of Articles 4, 5, and 6 of the official FIBA basketball rules. Methods: This study employed a quantitative descriptive approach. The participants were 60 basketball athletes competing in POPDA Grobogan. Data were collected through direct observation of the competition and the distribution of a structured test instrument related to official basketball rules. The data were analyzed using percentage techniques and presented visually. Results: The results indicated that 21 athletes (35%) were categorized as having a very good level of understanding, 36 athletes (60%) were in the good category, and 3 athletes (5%) were in the fairly good category. No athletes were classified in the poor or very poor categories (0%). Conclusion: In conclusion, the findings demonstrate that POPDA Grobogan athletes possess a high level of knowledge and mastery of the official basketball rules based on the 2022 standards established by FIBA.